PROGRESSIVE AND DIVERSION PROCESS: PROTECTION RULE AND ENFORCEMENT OF THE JUVENILLE JUSTICE - Junimart Girsang; Ninne Zahara Silviani (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
The implementation of juvenile justice with a progressive legal approach deserves to be used in child law enforcement because it prioritizes the interests of child protection. The relevance of progressive law enforcement to the juvenile justice system in Indonesia rests on the objectives of the juvenile justice system and the existence of rules for arrest, detention, and sentencing of crimes as an effort and form of sanctions against children, which can be in the form of treatment placed in the juvenile justice constitution. This research uses the juridical-normative method, namely legal analysis conducted by reviewing library materials or secondary data, and the data will be analysed through qualitative methods. This study aims to make law enforcers apply progressive law maximally in law enforcement of juvenile justice. The results of this study indicate that law enforcement for juvenile criminal justice in Indonesia is generally still far from the will of law enforcement with a progressive legal approach, and diversion is the right way to decide child criminal cases.